KONSEP HARTA DALAM TINJAUAN MAQASHID AL-SYARIAH - Muannif Ridwan (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2022)
This study aims to describe the concept of maintaining property in maqashid al-syariah and its relationship with property. In maqashid al-syariah property becomes one of the important topics that get attention so that people can maintain their property as well as possible. In the teachings of Islam it is also said that the use of wealth must be in the way of Allah and must always serve Allah. Islam has given more special attention to the property owned so that it can provide the value of worship in the sight of Allah SWT so that a happier life is achieved in this world and the hereafter. In this study the author uses a type of library research or also known as Library Research. This study concludes that property and ownership is one of the most important topics of discussion in Islamic law. Its position is related to one another, this is evidenced by the maqashid al-syariah method in which there are five elements, one of which discusses property (hifzh al-mal). The relationship between property and maqashid al-syariah, among others, is in the form of circulation and circulation, which aims to make the assets owned move in various circles, not only based on one group, and the next relationship lies in a condition that is far from problems so that it can avoid problems. danger and the relationship between property and maqashid al-syariah is with justice in managing assets.